Analysis of Truck Round Time Service Time in Import Delivery Activities at PT. Terminal Petikemas Surabaya - Andriani, Mita; Setiono, Benny Agus; Nasihah, Ainun (Universitas Hang Tuah, 2024)
This research aims to identify the main determinants that cause truck round time (TRT) service times to exceed standards and analyze their impact on operational efficiency at PT Terminal Petikemas Surabaya. Qualitative research methods with a triangulation approach were used to collect and analyze data. The research results show that the average annual TRT exceeds the standard of 30 minutes: 42.03 minutes (2021), 41.66 minutes (2022), and 41.38 minutes (2023). Key factors include crowding in the stacking yard, equipment problems, human resource skills and discipline, and adverse weather conditions. The impacts of high TRT include disruption of loading and unloading activities, increased operational costs, and decreased customer loyalty, which threatens the performance and sustainability of a company's business relationships.